2022
DOI: 10.1159/000524538
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intraoperative Cell Salvage in Cancer Surgery: An Updated Meta-Analysis of the Current Literature

Abstract: <b><i>Background:</i></b> Allogeneic blood transfusions in oncologic surgery are associated with increased recurrence and mortality. Adverse effects on outcome could be reduced or avoided by using intraoperative autologous blood cell salvage (IOCS). However, there are concerns regarding the safety of the autologous IOCS blood. Previous meta-analyses from 2012 and 2020 did not identify increased risk of cancer recurrence after using autologous IOCS blood. The objective of this review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 75 publications
0
18
0
2
Order By: Relevance
“…683 The use of ICS with a leukocyte depletion filter was not associated with significant differences in short-term complications, mortality or cancer recurrence in oncological patients undergoing radical prostatectomy, cystectomy, open nephrectomy or liver resection for colorectal liver metastases. [684][685][686][687][688] An updated meta-analysis of 34 observational trials showed a reduced RR for cancer recurrence and metastasis when ICS is used in cancer surgery. 688…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…683 The use of ICS with a leukocyte depletion filter was not associated with significant differences in short-term complications, mortality or cancer recurrence in oncological patients undergoing radical prostatectomy, cystectomy, open nephrectomy or liver resection for colorectal liver metastases. [684][685][686][687][688] An updated meta-analysis of 34 observational trials showed a reduced RR for cancer recurrence and metastasis when ICS is used in cancer surgery. 688…”
Section: Prothrombin Complex Concentratementioning
confidence: 99%
“…Recent studies have begun to challenge the convention that intraoperative blood conservation strategies, such as autotransfusion, are precluded in patients undergoing CRC surgery due to both infection risk and the risk that autotransfusion may reintroduce cancer cells. 40,49 There is evidence that autotransfusion may be less immunosuppressive and associated with decreased risk of CRC recurrence relative to allogenic transfusion. 45,50 Despite this, intraoperative blood conservation and autotransfusion are not commonly employed for CRC cancer surgery.…”
Section: Adverse Effects Of Blood Transfusionsmentioning
confidence: 99%
“…In major surgery, often autologous cell salvage is performed to re-transfuse the patient‘s own red blood cells. In 2022, Fischer et al have summarized the most recent evidence for the use of autologous cell salvage in cancer patients [8 ▪▪ ]. The authors summarize that cell salvage can also be used in cancer patients, if surgery is performed without touching the area of cancer, or with the use of leukocyte depletion filters, that have been shown in numerous studies to wash out cancer cells prior to re-transfusion of the patient‘s own blood.…”
Section: Autologous Cell Salvagementioning
confidence: 99%